TEACHER COMMUNICATION STRATEGIES IN TEACHING ENGLISH FOR SPECIAL NEED STUDENTS - Fahrinawati; Ahmad Darussalam; Alfiansyah Noor (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2025)
Abstract The objective of the research is to find out communication strategies used by the English teachers in Special need student classroom. The researcher used descriptive qualitative research and the data were collected by using observation, interview, and documentation (video recording). The result revealed that communication strategies used by the English teacher were circumlocution, approximation, use of nonlinguistic means (mime or gesture), literal translation, code switching, appeal for help, stalling or time-gaining strategies. The result of the interview showed that the communication strategies helped the students understood the meaning of words and instruction, made the students easier to understand the material, helped students to understand what the teacher said, helped to explain the material in teaching and learning process.